A Body of Dissatisfaction: a Study of the Effects of Media Imperialism in Kuwait - Mitchell, Charles; Dinkha, Juliet; Kononova, Anastasia; Matta, Monica (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> Media has an enduring reputation of affecting perception. Perpetuating unrealistic body standards is just one way mediated messages influence negatively an audience. In the last 25 years, Kuwait has seen an invasion of western media including TV, music, magazines and movies. We decided to tackle the subject of the effects of this cultural imperialism to see if the prevalence of these imported western body images were having a negative impact. The social comparison theory states that individuals evaluate themselves through comparison even with media images. This study examines how Western -- mainly -- U.S. media imperialism and the social comparison theory through media affects body perception by examining the effects of college-age young adults watching shows with prominent thin television characters compared to shows that had prominent average body types in the cast. We expect to find that exposure to programming with only thin characters will correlate with body dissatisfaction. The study included distributing 286 self-administered preliminary surveys to discover the most popular shows that college students (mostly 18 to 25 year olds) watched. After we identified the most popular shows, blind self-administered surveys were circulated to a sample of 240 college-age young adults (120 males and 120 females) to determine if any correlation could be made between their television show preferences and their body dissatisfaction. We found body image dissatisfaction is being reported, leading to the implication that media imperialism is eroding traditional Arab body image in Kuwait. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->